GOLD GEOCHEMISTRY IN POSTERUPTIVE ACTIVITY ON CINDER CONES PRODUCED ON THE NORTHERN FISSURE OF THE GREAT TOLBACHIK FLANK ERUPTION IN 1975-1976 - Serafimova E.K.; Kazmin L.A.; Dobroskok T.A. (My University, 2001)
New data are presented on the gold content of the eruptive and posteruptive exhalations of highly varying temperatures. Deposits that accumulated around fumarole vents show gold concentrations ranging from 0.05 to 2800 ppm in time and space. It is believed that volcanic fluids transported gold in compounds with chlorine, and that the source of gold and other metallic elements in posteruptive deposition was poorly degassed magnesian basalt which had been brought to the surface from a subcrustal source.